2011
DOI: 10.17221/4/2011-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Rural development in the context of agricultural "green" subsidies: Czech farmers' responses

Abstract: Abstract:The study compares the role of agricultural green subsidies in rural development of the czech republic before and after joining the European Union (EU) in 2004. We use the perspective of multifunctional agriculture and contribute to the research on the contemporary trends in czech agriculture by using the data collected through surveys in 2000 and 2006, as well as 2008 comparative statistical support, to ask if there have been significant changes and improvements in farmers' evaluations of these progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The level of education does not have much influence on risk perception, as was demonstrated by studies conducted in the Czech Republic (Vávra et al, 2014;Lapka et al, 2011). Jóhannesdóttir and Gísladóttir (2010, p. 418) have explained the correlation between disaster risk perception and vulnerability.…”
Section: Dpm 271mentioning
confidence: 87%
“…The level of education does not have much influence on risk perception, as was demonstrated by studies conducted in the Czech Republic (Vávra et al, 2014;Lapka et al, 2011). Jóhannesdóttir and Gísladóttir (2010, p. 418) have explained the correlation between disaster risk perception and vulnerability.…”
Section: Dpm 271mentioning
confidence: 87%
“…However, due to the high participation costs, farmers' involvement in this practice remains low (Li et al, 2020). Farmers' pro-environmental behaviors (PEBs) in agriculture are likely to be sustainable only if the benefits from their actions are sufficient to cover the production costs and further improve their families' livelihoods (Lapka et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Sophia et al [27] surveyed the impact of green schemes about agricultural production on the livelihood of communities in the Kavango Region, Namibia, and then they found that they should inculcate a change in attitude so as to encourage collaborative efforts between communities and the green scheme management which would impact on the livelihood of people positively. As for incentives to take actions of green agricultural production, Lapka et al [28] found that subsidy was effective based on the survey data of farmers in the Czech Republic. Further, Li et al [29] used Cournot model to find that the amount of green production investment increased with the green subsidy rate.…”
Section: Introductionmentioning
confidence: 99%